Fadhil Irawani, the II Shaikh al-Islam of Caucasian Muslims:between Facts and Contradictions - Aghamoghlanov, Hilal (Scholarya Demo Journal of Ruby, 2025)
The article explores the possibility of Fazil Irawani, known as the II Shaikh al-Islam of the Administration of Caucasian Muslims, occupying this role. The article also examines the leaders of the Mohammedan religious clergy based in Tiflis from 1823 to 1873, utilizing historical data, calendars, and published articles from that era. In order to create a clear image for the reader, information about the essence of the title of Shaikh al-Islam, its history, and its use in our religious and political context has been introduced. The similarity of their names and certain resemblance between Shaikh al-Islam Akhund Mullah Muhammad, who lived in Yerevan and Mullah Muhammad Fadhil Irawani from Najaf led the author of the book Islam and Shaikh al-Islam in the Caucasus to assume that they were the same person, and as a result, he presented him as the Second Shaikh al-Islam of Caucasian Muslims. Regarding Shaikh al-Islam Akhund Mullah Muhammad, who resided in Yerevan, documentary evidence suggests his birth year was 1771.The article explores the reasons he was called Shaikh al-Islam and reveals evidence suggesting that during the Qajar rule, he was appointed as the official Shaikh al-Islam of the Irawan Khanate. Due to his reputation among the people and his spiritual respect, he was accepted as a Shaikh al-Islam in Tsarist Russia and continued as the head of the Qadavat and Sharia court in the Irawan province. The article demonstrates that they are completely different in many ways: their patronymics, dates of birth and death, places of education, places of burial, and the number and names of their children. In Tiflis, different people were named Muslim leaders when Irawani was claimed to be Shaikh al-Islam. It’s clear that each of these two people has identifiable information. In the above-mentioned book, those data were combined into a single image, and all facts and information were attributed to that person.